Upgradation to Improve Seed Quality in Bambusa bambos - Renganayaki, P. R.; Ramamoorthy, K. (Indian Forester, 2017)
In view of the lower germination percentage observed owing to the presence of high level of chaffy and ill filled seeds, attempts were made to improve seed quality through water and salt floatation methods. Seed graded with 15 per cent salt solution enhanced germination and seedling vigour, however the recovery of good quality seeds was low. Liquid floatation method of grading using water (for 10 min) and salt solution (for 10 minutes) were at par with each other recording good recovery (73 to 74%) of sinkers. Seed up gradation using water for 10 min was found suitable for seed quality improvement of Bambusa bambos.